Tinjauan Pustaka tentang Manajemen Pendidikan Cerdas: Mengintegrasikan Kecerdasan Buatan dan Kepemimpinan Digital untuk Inovasi Institusional : English - Mabsus, Parosil; Handoko, Handoko; Hasan Hariri, Hasan Hariri (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2026)
This study aims to analyze the conceptual framework of smart education management through the integration of artificial intelligence (AI) and digital leadership in driving institutional innovation. The study employs a qualitative approach using the Systematic Literature Review (SLR) method, synthesizing five key studies related to AI readiness, digital leadership, human resource capacity, and the challenges of digital transformation in education. The findings indicate that the success of digital education transformation is determined not only by technology adoption but also by the alignment between organizational readiness, leadership capacity, and human resource development. AI serves as an enabler, while digital leadership functions as a strategic driver that directs the utilization of technology toward meaningful institutional change. Furthermore, human resource capacity particularly teachers’ digital competencies is a key factor in ensuring effective technology implementation, while challenges such as infrastructure limitations and organizational resistance influence the transformation process. This study produces a conceptual framework that positions institutional innovation as the result of a dynamic interaction among these variables. Theoretically, this study integrates perspectives on transformational, instructional, distributed, and adaptive leadership to understand smart educational management. Practically, the study’s findings emphasize the importance of developing adaptive, collaborative, and data-driven leadership models to support sustainable educational innovation in the era of artificial intelligence